Media attention to locations and the cross‐section of stock returns. (9th July 2020) - Tang, Guomei; Zhang, Xueyong
Abstract: This paper investigates the relationship between media attention to a location and the price behaviour of stocks headquartered there. Using monthly media coverage of 236 prefecture‐level cities in mainland China, we find that stocks in cities with higher abnormal media attention outperform stocks in cities with lower abnormal media attention by 3.72 percent per year, and the positive relationship between attention and returns holds after controlling for firm characteristics, firm‐level attention proxies and local economic conditions. Moreover, the initial positive price pressure is completely reversed within three months. Our results remain robust when we take endogeneity and other concerns into account.